Premedication practices for neonatal tracheal intubation: Results from the EPIPPAIN 2 prospective cohort study and comparison with EPIPPAIN 1. Issue 2 (4th April 2021) - Walter‐Nicolet, Elizabeth; Marchand‐Martin, Laetitia; Guellec, Isabelle; Biran, Valérie; Moktari, Mostafa; Zana‐Taieb, Elodie; Magny, Jean‐François; Desfrère, Luc; Waszak, Paul; Boileau, Pascal; Chauvin, Gilles; de Saint Blanquat, Laure; et al.
Abstract: To describe the frequency and nature of premedication practices for neonatal tracheal intubation (TI) in 2011; to identify independent risk factors for the absence of premedication; to compare data with those from 2005 and to confront observed practices with current recommendations. Data concerning TI performed in neonates during the first 14 days of their admission to participating neonatal/pediatric intensive care units were prospectively collected at the bedside. This study was part of the Epidemiology of Procedural Pain in Neonates study (EPIPPAIN 2) conducted in 16 tertiary care units in the region of Paris, France, in 2011. Multivariate analysis was used to identify factors associated with premedication use and multilevel analysis to identify center effect. Results were compared with those of the EPIPPAIN 1 study, conducted in 2005 with a similar design, and to a current guidance for the clinician for this procedure. One hundred and twenty‐one intubations carried out in 121 patients were analyzed. The specific premedication rate was 47% and drugs used included mainly propofol (26%), sufentanil (24%), and ketamine (12%). Three factors were associated with the use of a specific premedication: nonemergent TI (Odds ratio (OR) [95% CI]: 5.3 [1.49‐20.80]), existence of a specific written protocol in the ward (OR [95% CI]:4.80 [2.12‐11.57]), and the absence of a nonspecific concurrent analgesia infusion before TI (OR [95% CI]: 3.41 [1.46‐8.45]). No center effect was observed. The specific premedication rate was lower than the 56% rate observed in 2005. The drugs used were more homogenous and consistent with the current recommendations than in 2005, especially in centers with a specific written protocol. Premedication use prior to neonatal TI was low, even for nonemergent procedures. Scientific consensus, implementation of international or national recommendations, and local written protocols are urgently needed to improve premedication practices for neonatal intubation.